2022
DOI: 10.1007/s10942-022-00467-x
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitions About Health in Relation to Coronavirus Anxiety: The Mediating Role of Cognitive Attentional Syndrome and Distress Tolerance

Abstract: The current study aimed to investigate the mediating role of cognitive attentional syndrome (CAS) and distress tolerance in the relationship between health-related metacognitions and coronavirus anxiety. The sample of this study consisted of 462 participants (381 female). Participants voluntarily completed self-report questionnaires on each of the variables mentioned above. The results of the structural modeling analysis showed that health-related metacognitions have a significant effect on the mediator variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
(61 reference statements)
1
3
1
Order By: Relevance
“…41 Vahidi far et al 59 Mohammadi et al 42 Mohammad Khani and Zafarpanahi. 60 However, the results of studies done by Alavi et al 51 Orsal et al 61 and Fonia et al, 62 in which girls' rate of internet addiction prevalence was higher than boys', were inconsistent with the results of the present study. Male students seem to have more internet addiction than female students do.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…41 Vahidi far et al 59 Mohammadi et al 42 Mohammad Khani and Zafarpanahi. 60 However, the results of studies done by Alavi et al 51 Orsal et al 61 and Fonia et al, 62 in which girls' rate of internet addiction prevalence was higher than boys', were inconsistent with the results of the present study. Male students seem to have more internet addiction than female students do.…”
Section: Discussioncontrasting
confidence: 82%
“…42 Mohammad Khani and Zafarpanahi. 60 However, the results of studies done by Alavi et al. 51 Orsal et al.…”
Section: Discussionmentioning
confidence: 98%
“…This highlights the importance of cognitive factors in the maintenance of COVID-19 related distress. These findings mirror the findings of Mohammadkhani et al (2022) , highlighting that dysfunctional beliefs and ruminations about the pandemic were significant predictors of COVID-19 related anxiety. Research carried out by Faustino et al (2022) further highlighted the role of negative cognitions as predictors of COVID-19 related distress.…”
Section: Discussionsupporting
confidence: 74%
“… Asmundson & Taylor, 2020 ; Ehlers & Clark, 2000 ; Rachman, 2012 ; Salkovskis & Warwick, 2001 ). A recent study by Mohammadkhani, Akbari, Shahbahrami, Seydavi, and Kolubinski (2022) examined the role of Cognitive Attentional Syndrome in relation to COVID-19, which highlighted that dysfunctional beliefs and ruminations about the pandemic were significant predictors of COVID-19 related anxiety. Furthermore, increases in attentional control were linked to lower levels of rumination and, in turn, lower levels of COVID-19 related distress ( Guo, Yang, Elhai, & McKay, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Strategies such as mandatory lockdowns and quarantine, which forced people to stay in their homes and maintain physical distance, led to exhaustion, detachment from others, anxiety, stress responses, and irritability (Bonanno, 2004; Rubin & Wessely, 2020). Elevations in depression and anxiety (Y. Huang & Zhao, 2020; Lei et al, 2020), obsessive–compulsive symptoms (Guzick et al, 2021), post‐traumatic stress symptoms (Cénat et al, 2021; Janiri et al, 2021), sleep problems (Jahrami et al, 2021), boredom, irritability and disappointment (Brooks et al, 2020), health anxiety (Akbari, Spada, et al, 2021; Mohammadkhani et al, 2022), substance use (Wei & Shah, 2020), grief and complicated grief (Diolaiuti et al, 2021; Wallace et al, 2020), suicide (Sher, 2020) and worsened quality of life (Melo‐Oliveira et al, 2021) are some of the adverse psychological outcomes that have been reported by researchers across different countries. Such adverse mental health consequences were evident and reported in all segments of the population, for example, the general population (Béland et al, 2020; Wang et al, 2020), individuals affected by COVID‐19 (Nguyen et al, 2020; Zhao et al, 2020), healthcare workers (Cao et al, 2020; J.…”
Section: Introductionmentioning
confidence: 99%